Experimental study on initial loss of tension in bolted joints. (June 2016) - Zhu, Linbo; Hong, Jun; Yang, Guoqing; Jiang, Xiangjun
The initial loss of tension in individual bolts after initial tightening obviously affects the level and the stability of the clamp load in bolted joints. A high-precision instrument to analyze the clamp load loss was developed. In this instrument, an Atlas Copco's high performance spindle with an accuracy of ±2.5% under the conditions of one million duty cycles was used to tighten the test bolts and nuts. A rotary torque-angle transducer was integrated in the tightening spindle to measure the tightening torque. KMR force washer with a repeatability of < ±1% was applied to monitor the clamping force in real time. Using this instrument, the design of experiment analysis was performed to determine the effect of variables on the initial loss of tension. Those variables included the joint materials, the fastener class, the gasket grade, the lubrication, the surface roughness, the tightening speed, and the number of repeated tightening. The results showed that the tightening speed and the number of repeated tightening had a significant effect on the initial loss of tension. Moreover, a process criterion of eliminating plastic deformation was proposed to minimize the initial loss of tension. The findings presented in this paper will be expected to enhance the reliability and the safety of bolted assemblies, especially in critical applications.